Meteorological aspects of particle dispersal - Emberlin, Jean (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2003)
The main meteorological factors that influence particle dispersal are atmospheric stability, wind direction and speed, and precipitation. The troposphere, the lowest layer of the atmosphere, contains 75% of the total molecular or gaseous mass of the air and nearly all the water vapour and aerosols. The airborne particle diffusion, transport and precipitation depend on the wind speed, its direction and rainfalls. Meteorological factors, which control the patterns of particle dispersal, have an important influence on their air concentrations.